Efficiency of secondary traits for improving maize for low-nitrogen target environments - Bänziger, M.; Lafitte, H.R. (Wiley, 1997)
Consideration of secondary traits could improve selection efficiency under stress conditions. This study assesses the value of secondary traits for improving lowland tropical maize (Zea mays L.) for low‐N target environments. Nineteen experiments grown with no N applied at CIMMYT, México, between 1986 and 1995 were analyzed for grain yield, anthesis‐silking intervai (ASI), number of ears per plant, leaf chlorophyll concentration, and an estimate of leaf senescence. Broad‐sense heritabilities of traits, genetic correlations between secondary traits and grain yield, and predicted response of grain yield to selection for single or multiple traits were calculated. Multiple traits were combined using an unrestricted selection index (Smith‐Hazel index). Broad‐sense heritabilities averaged 0.46 for grain yield, 0.52 for ASI, 0.44 for ears per plant, 0.35 for leaf chlorophyll concentration, and 0.60 for leaf senescence. Genetic correlations of secondary traits with grain yield averaged −0.47 for ASI, 0.78 for ears per plant, 0.24 for leaf chlorophyll concentration, and 0.42 for leaf senescence. Direct selection for grain yield was superior to selection for single secondary traits in most experiments. When information on all traits was combined in a Smith‐Hazel index, selection efficiency improved by 14% on average over selection for grain yield alone. Among secondary traits, ears per plant and leaf senescence discriminated high‐yielding genotypes the best. Leaf chlorophyll concentration, and in some instances ASI, provided information on environmental variation within experiments. We conclude that secondary traits can increase the efficiency of selection for grain yield in maize breeding programs targeting low‐N environments.